CURRENT PROBLEMS OF DOMESTIC PRACTICE OF INCOME AND EXPENSES FORMATION OF COMMERCIAL BANKS - LOPATOVSKA, Oksana; BOROLYUK, Maxim (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the current issues of income and expenses of commercial banks in Ukraine in the context of martial law, political instability and economic turbulence. The author emphasizes that the efficiency of banking activities directly depends on the ability of banks to generate profitable income and control the cost side. The author analyzes the dynamics, structure and composition of the main items of income and expenses of banking institutions for the period of 2021-2024. The main attention is paid to interest income and expenses as key components of banks' profitable activities, as well as general administrative expenses, the level of which shows a steady upward trend. The impact of asset provisions, a decrease in business activity and an increase in the cost of resources on the formation of unprofitability of individual institutions is revealed. It is found that, despite the challenges, the banking sector of Ukraine retains the ability to generate profits, but the growth rate of expenses exceeds the growth rate of income, which indicates potential risks of loss of financial stability. The paper also examines the factors that cause the unprofitability of individual banking institutions and substantiates possible ways to reduce costs and increase the efficiency of banking activities. The author proposes a set of measures to intensify lending and commission activities, automate processes, reduce administrative costs and introduce new financial technologies. Considerable attention is paid to the issue of optimizing the expenditure side of bank budgets, taking into account current market conditions and customer needs. The author proves that the strategic task of banks is to increase profitable assets, improve the efficiency of operations and implement digital solutions. The proposed approaches to income and expense management are of practical importance and can be used to improve the financial performance of both individual banks and the banking system as a whole.
Keywords: commercial bank; income; expenses; profit; profitability; lending activities; commission operations; bank reserves